Characterizing Wellness Initiatives in Academic Radiation Oncology Departments - Sara Beltrán Ponce, MD; Crystal Seldon Taswell, MD; Idalid Franco, MD, MPH; Malcolm D. Mattes, MD; Tracy Kelly, MD; Leah Katz, MD, MPH (Advances in Radiation Oncology)
Purpose: Burnout is prevalent in radiation oncology (RO), and an increased focus on promoting physician wellness and formalizing wellness-directed efforts has transpired in recent years. We aimed to characterize current wellness leadership positions and efforts within academic RO departments. Methods and Materials: Academic RO department chairs were contacted to inquire whether they had a departmental wellness leader with a request for leader contact information, if applicable. Wellness leaders were invited to complete an anonymous survey in January and February 2023 using Qualtrics. Questions assessed leader demographic characteristics, role structure and resources, current initiatives, and impacts to date. Descriptive statistics and summaries of free-text responses are reported. Results: A total of 120 chairs were contacted. In total, 71 (59%) responded, with 43 (61%) having departmental wellness leaders, of which 17 (39.5%) responded, to the survey. A total of 70.6% were female, and 76.5% were physician faculty. Most respondents were early-career. The most common previously implemented initiatives included offering programming and education (33.3%) and improved access to mental health services (25%). The most common active initiatives include conducting studies to address root causes of burnout (41.7%), developing specific wellness goals (25%), performing a review of policies that encourage prolonged work hours (25%), and offering programming and education (25%). Challenges included limited bandwidth (66.7%), lack of funding (41.7%), and lack of departmental interest in organizing or attending events (33.3%). Leaders highlight the importance of a dedicated individual to tangibly implement changes and the unique opportunity of someone within RO to understand the specific challenges faced by those in our field. Conclusions: Wellness leadership roles exist in many RO departments. As evidenced by a limited number of fully implemented initiatives, these roles are new and evolving. A focus on wellness has the potential to bring positive change to departments; however, the impact of newly established wellness roles on culture and balance requires longitudinal followup.